Effect of Professionalism and Work Discipline on Employee Performance Through Employee Development Programs as an Intervening Variable - Kinasih, Ramona Dwi; Firdaus, Vera; Andriani, Dewi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the effects of professionalism and work discipline on employee performance at PT X, with the Employee Development Program serving as an intervening variable. Methodology: A descriptive quantitative research design was employed, utilizing purposive sampling techniques with 100 respondents. Data were analyzed using SmartPLS software, including Outer Model Test analysis, Cronbach’s Alpha, Average Variance Extracted (AVE), Composite Reliability, R², and estimates for path coefficients. Results: The results indicate that professionalism positively affects employee performance (T = 2.639, p = 0.009) and enhances employee development programs (T = 2.344, p = 0.019). Work discipline, while negatively affecting performance (T = 1.784, p = 0.075), significantly positively influences employee development programs (T = 4.764, p = 0.000). Employee development programs are found to significantly improve performance (T = 3.890, p = 0.000). Findings: The study highlights that professionalism and employee development programs play a critical role in enhancing employee performance, while work discipline, despite its positive impact on development programs, does not have a significant direct effect on performance. Novelty: This research provides new empirical insights into the interplay between professionalism, work discipline, and employee development programs, emphasizing their impact on employee performance. Originality: The study is original in its focus on the mediating role of employee development programs in the context of professionalism and work discipline. Conclusions: Professionalism and structured development programs are key to enhancing employee performance. Type of Paper: Empirical research paper.